2010
DOI: 10.1177/0146167210362789
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Expression of Implicit Stereotypes: Reflexive Control Through Implementation Intentions

Abstract: The authors tested the effectiveness of implementation intentions as a strategy for limiting the behavioral expression of implicit stereotypes. Implementation intentions are if-then plans that link an intended response to an anticipated situational cue, thereby enabling a reflexive form of control. The authors examined whether two different types of implementation intentions could improve response accuracy on the Shooter Task, a reaction time measure of implicit stereotyping. In Study 1, participants used a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(130 citation statements)
references
References 43 publications
7
118
0
5
Order By: Relevance
“…In one, for example, participants are exposed to images of people who defy stereotypes (e.g., admired Black people / hated White people; Joy-Gaba & Nosek, 2010). In another, participants are given goals to override implicit biases (e.g., Mendoza, Gollwitzer, & Amodio, 2010;Stewart & Payne, 2008).In most of the research on implicit association change, the short-term malleability of associations is tested by administering an implicit measure immediately after the intervention. Studies examining long-term change in implicit associations are rare.…”
mentioning
confidence: 99%
“…In one, for example, participants are exposed to images of people who defy stereotypes (e.g., admired Black people / hated White people; Joy-Gaba & Nosek, 2010). In another, participants are given goals to override implicit biases (e.g., Mendoza, Gollwitzer, & Amodio, 2010;Stewart & Payne, 2008).In most of the research on implicit association change, the short-term malleability of associations is tested by administering an implicit measure immediately after the intervention. Studies examining long-term change in implicit associations are rare.…”
mentioning
confidence: 99%
“…Recent research has convincingly shown that implementation intentions can be effective in overruling habitual behaviors when specifying that the habitual response shall be replaced with an alternative new response once the critical situation is encountered Cohen et al, 2008;Holland et al, 2006;Mendoza et al, 2010;Schweiger Gallo et al, 2009;Schweiger Gallo & Gollwitzer, 2007;Stewart & Payne, 2008). In the present research, we investigated the cognitive effects of forming counterhabitual implementation intentions to increase the understanding of what makes counterhabitual implementation intentions such effective tools to overrule habits.…”
Section: Discussionmentioning
confidence: 97%
“…Counterhabitual implementation intentions have been found effective in changing several types of habits, such as recycling habits (Holland et al, 2006), reducing switch costs in a task-switching paradigm and overcoming the automatic effects of spatial location in a Simon task (Cohen et al, 2008), reducing automatic stereotypical thoughts (Stewart & Payne, 2008) or limiting the behavioral expression of implicit stereotypes (Mendoza, Gollwitzer, & Amodio, 2010), reducing spider fear in spider phobics (Schweiger Gallo & Gollwitzer, 2007;Schweiger Gallo, Keil, McCulloch, Rockstroh, & Gollwitzer, 2009), reducing prompted disgust reactions (Schweiger Gallo et al, 2009), decreasing unhealthy snack consumption , and reducing smoking behavior (but only for people with weak or moderately strong smoking habits; Webb, Sheeran, & Luszczynska, 2009). …”
Section: Implementation Intentions As a Strategy For Breaking Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…increasing controlled processing and reducing the impact of automatic stereotypic associations (Mendoza, Gollwitzer, & Amodio, 2010).…”
Section: Implementation Intentionsmentioning
confidence: 99%